Orbitofrontal cortex volume links polygenic risk for smoking with tobacco use in healthy adolescents - Li, Jin; Liu, Bing; Banaschewski, Tobias; Bokde, Arun L. W.; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Ittermann, Bernd; et al. (Psychological medicine, 2022)
BackgroundTobacco smoking remains one of the leading causes of preventable illness and death and is heritable with complex underpinnings. Converging evidence suggests a contribution of the polygenic risk for smoking to the use of tobacco and other substances. Yet, the underlying brain mechanisms between the genetic risk and tobacco smoking remain poorly understood.MethodsGenomic, neuroimaging, and self-report data were acquired from a large cohort of adolescents from the IMAGEN study (a European multicenter study). Polygenic risk scores (PGRS) for smoking were calculated based on a genome-wide association study meta-analysis conducted by the Tobacco and Genetics Consortium. We examined the interrelationships among the genetic risk for smoking initiation, brain structure, and the number of occasions of tobacco use.ResultsA higher smoking PGRS was significantly associated with both an increased number of occasions of tobacco use and smaller cortical volume of the right orbitofrontal cortex (OFC). Furthermore, reduced cortical volume within this cluster correlated with greater tobacco use. A subsequent path analysis suggested that the cortical volume within this cluster partially mediated the association between the genetic risk for smoking and the number of occasions of tobacco use.ConclusionsOur data provide the first evidence for the involvement of the OFC in the relationship between smoking PGRS and tobacco use. Future studies of the molecular mechanisms underlying tobacco smoking should consider the mediation effect of the related neural structure.
Gesehen am 16.11.222